Transaction convenience in the payment stage: the retailers' perspective. Issue 5 (19th August 2014) - Lundberg, Heléne; Öhman, Peter; Sjödin, Ulrika
Abstract : Purpose: We aim to shed light upon how retailers view alternative payment forms and to what extent they are willing to risk offending their customers by imposing payment restrictions. Design/methodology/approach: This exploratory study consists of three consecutive parts: (1) 100 situations of paying for goods or services, (2) interviews with 25 of these 100 retailers, and (3) observations at a meeting between retailers and bank representatives on various aspects of card and cash payments. Findings: Retailers are unwilling to risk offending their customers and do not normally undertake any actions to affect the customers' choice of payment form, except for proactively or reactively excluding the use of certain expensive credit cards, and card payments for small amounts. The retailers only take the risk of causing customer dissatisfaction when they feel that the sacrifice for not doing so is too costly, and in these cases the salespersons act very late in the purchase process. Other aspects than payment costs (such as safety, time and environment) seem to have little impact on individual retailers' actions at the payment stage. Research limitations/implications: The present study focuses solely on the retailers' point of view on the payment stage, implying a need for additional research on customers' and bank representatives' views on the same matter. Practical implications: Retailers try to nurture their customer relationships also when they are proactive or reactive, i.e. by pointing to the high cost of a particular payment form and/or asking customers to help with small change. Sending signals that invite customers to assist may not only be a way to affect how customers pay, but also foster relationship development. Originality/value: No previous study has focused on the way selling companies approach their customers at the payment stage in terms of proactive, reactive and inactive behaviour.